2011
DOI: 10.1128/ec.00002-11
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Host Cells as the Major Contributor of Lipids in the Intravacuolar Network of Toxoplasma-Infected Cells

Abstract: The intracellular parasite Toxoplasma gondii develops inside a parasitophorous vacuole (PV) that derives from the host cell plasma membrane during invasion. Previous electron micrograph images have shown that the membrane of this vacuole undergoes an extraordinary remodeling with an extensive network of thin tubules and vesicles, the intravacuolar network (IVN), which fills the lumen of the PV. While dense granule proteins, secreted during and after invasion, are the main factors for the organization and tubul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 20 publications
(17 reference statements)
3
63
0
1
Order By: Relevance
“…Our results suggest that T. gondii -infected SkMC increases the synthesis of LD as well as their content, providing lipids to the parasite and thus contributing to the growth and maturation of the parasitophorous vacuole, as described in another cellular model by Caffaro et al [38]. Initially using the fluorescent dye Nile Red, it was possible to observe the increased formation of LD within the first hour of T. gondii- SkMC interaction and also the presence of LDs next to the parasite, and at 24 h around the PV.…”
Section: Discussionsupporting
confidence: 73%
“…Our results suggest that T. gondii -infected SkMC increases the synthesis of LD as well as their content, providing lipids to the parasite and thus contributing to the growth and maturation of the parasitophorous vacuole, as described in another cellular model by Caffaro et al [38]. Initially using the fluorescent dye Nile Red, it was possible to observe the increased formation of LD within the first hour of T. gondii- SkMC interaction and also the presence of LDs next to the parasite, and at 24 h around the PV.…”
Section: Discussionsupporting
confidence: 73%
“…To monitor FA import we pulse-labeled PV-infected HeLa cells with a fluorescent fatty acid Bodipy 500/510 C4, 9 (bodipy-FA) which is believed to mimic FA with 18 carbon atoms backbone. This and similar molecules are extensively used in lipid metabolism research and it was previously shown to be rapidly utilized by cellular lipid synthesis machinery and incorporated into phospholipids, triglycerides and other natural lipids [24], [25], [26], [27], [28]. The cells were infected at a multiplicity of 50 PFU/cell to ensure simultaneous development of infection, and bodipy-FA was added for 30 min at 4 hours post infection (h p.i.…”
Section: Resultsmentioning
confidence: 99%
“…The IVN, a network of tubules and vesicles, is generated from proteins and lipids secreted by the parasite as well as lipids scavenged from the host cell, including phosphatidylcholine, cholesterol from host low density lipoproteins (LDL), and sphingolipids from the host Golgi (21,(62)(63)(64)(65). The distribution of TgLCAT to the IVN suggests a role for this enzyme in the remodeling of the IVN membranes by producing lysophosphatidylcholine that can shape membranes and change their curvature.…”
Section: Discussionmentioning
confidence: 99%